The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1109/66.401001
|View full text |Cite
|
Sign up to set email alerts
|

Thermal uniformity and stress minimization during rapid thermal processes

Abstract: Abstruct-The practical development and implementation of rapid thermal processes will significantly influence the semiconductor fabrication industry. With the capability to perform heat cycles quickly and with low thermal budgets, rapid thermal processors have the potential to supplant conventional thermal systems in the years to come. Currently, rapid thermal processors are unable to match the thermal process uniformity produced in conventional convective-based systems. Using a thermal model to approximate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…4. Equation (4) (4) shows the relationship between the acceptance angle and incident plane distance and refraction index ratio . Based on this equation, Fig.…”
Section: Acceptance Angle and Aperturementioning
confidence: 99%
See 1 more Smart Citation
“…4. Equation (4) (4) shows the relationship between the acceptance angle and incident plane distance and refraction index ratio . Based on this equation, Fig.…”
Section: Acceptance Angle and Aperturementioning
confidence: 99%
“…A CCURATE measurement of surface temperature distribution is a great concern in the semiconductor industries since any temperature nonuniformity may cause significant defects in the components deposited on wafers [4]. As an industrial tool for temperature measurement, light-pipe radiation thermometers (LPRTs) are becoming increasingly important.…”
Section: Introductionmentioning
confidence: 99%
“…Bentini et al [6] found the strip heater induces much lower thermal stresses than the irradiation of a free wafer. Furthermore, Perkins et al [7] used a nodal analysis to discuss the thermal uniformity and stress minimization during the steady state and transient phase of RTP. Jan and Lin [8] studied lamp configuration design for RTP systems to achieve the necessary temperature uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…Single-wafer rapid thermal processing (RTP) has become an alternative to the conventional furnace-based batch processing in many processes [1], [2]. To obtain uniform processing across the wafer and to prevent the creation of slip defects due to thermal stresses, the temperature must be nearly uniform on the wafer throughout the process cycle [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al [10] optimized the incident heat flux profile over a wafer by determining the heat loss profiles using Lord's thermal model [3], which simulates radial temperature gradients by assuming uniform temperature through the wafer thickness. Following the work of Riley and Gyurcsik [9], Perkins et al [2] used their special wafer-edge node analysis to show that idealized intensity profiles can maintain thermal uniformity at steady-state temperatures, and that dynamic continuously changing profiles are required to maintain temperature uniformity during thermal transients. The works mentioned above describe quantifying incident heat flux over a wafer to achieve the necessary thermal uniformity requirement during RTP.…”
Section: Introductionmentioning
confidence: 99%